THE EFFECT OF MORINGA LEAVES AND SNAKEHEAD FISH BISCUIT SUPPLEMENTATION ON THE NUTRITIONAL STATUS OF MALNOURISHED AND UNDERWEIGHT TODDLERS - Yunita Yunita; Kusdalinah Kusdalinah; Okdi Natan (Poltekkes Kemenkes Bengkulu, 2022)
Malnourished toddlers are directly linked to a lack of energy and protein and infectious disorders like worms. Handling toddlers malnutrition and worm infection might be accomplished by providing supplementary food formulas with consideration for nutrition, health benefits, resource, durability, and the pre-eminence of local food, for example, in the form of biscuits modified with moringa leaves and snakehead fish. The objective of this research is to assess the effect of providing malnourished toddlers with biscuits modified with moringa leaves and snakehead fish on their nutritional condition. This research was classified as an experimental research with Pre and Post Randomized Controlled Group Design. The subjects were toddlers between the ages of 24 to 59 months with malnutrition and worm infection. Each group (malnourished and worm-infected group, malnourished group, and control) consisted of 14 toddlers and was determined by purposive sampling. The research was conducted for two months with the intervention of providing modified biscuits. The modified biscuits were given as much as 60 gr twice daily for two months. The intervention was monitored and evaluated every two weeks. The data were analyzed using the Wilcoxon test, Kruskal Wallis, and Binary Logistic Regression. The provision of biscuits modified with moringa leaves and snakehead fish resulted in a significant increase in nutritional status (p = 0.008), and a distinct increase in nutritional status among malnourished toddlers (p = 0000). The biscuits modified with Moringa leaves and snakehead fish can be used as an alternative snacks to improve the nutritional status of underweight toddlers.